Transmission of Hadroh Kuntulan Banyuwangi Art through Community-Based Art Education - Saryanto; Arini, Sri Hermawati Dwi; Supriadi, Didin; Turnip, Yehezkiel Petrus; Srimoko, Gandung Joko; Tarwiyah, Tuti (Institut Seni Indonesia Denpasar, 2025)
This research explores cultural strategies through education, specifically focusing on Community-Based Art Education (CBAE) in Banyuwangi. In order to achieve the stated objective, a qualitative descriptive method was adopted to examine the Kuntulan art form, particularly Hadroh Kuntulan. The art form consisted of playing Hadroh music accompanied by sholawat singing and pencak silat movements that have evolved into dance. This investigation was conducted in Banje Hamlet, Bubuk Village, Rogodjampi District, Banyuwangi Regency, East Java, at Islamic Junior High School 8 & Art Studio Gholet Dhulur. The location was selected primarily due to the presence of the Using tribe, which, unlike more well-known groups such as the Baduy and Sasak tribes, remains relatively unknown. Typically, cultural transmission through Community-Based Art Education (CBAE) is facilitated by integrating educational institutions. Within the context of the present exploration, this studio played a central role. In Indonesia, art education is usually incorporated into a school's intracurricular and extracurricular curriculum. These institutions typically form school-age music groups comprising students from various schools. Within this construct, schools and social institutions function as program planners, students as learners, and the broader community as a source of cultural knowledge. The results obtained from this study show that the integration of cultural arts into the school curriculum through partnerships with social institutions plays a crucial role in preserving cultural heritage. It also emphasized that the resilience of these cultural traditions is sustained through the active support and inclusiveness of the community.